The soldier's story of his captivity at Andersonville, Belle Isle, and other Rebel prisons. - Goss, Warren Lee, 1835-1925 (Online access with subscription: Proquest Ebook Central., 2001)
Warren Lee Goss was a prisoner at Andersonville Prison during the Civil War. His book, The Soldier's Story, is his unexaggerated record of a survivor of the horrors of this prison camp. Through agonizing memories he regards this story as a work of solemn duty rather than a work of pleasure.